HOLDING THE LINE. - MILLS, MARA (Artforum International, 2025)
The article highlights Christine Sun Kim's impactful public art and multimedia practice, which foregrounds Deaf culture and redefines sound and communication through visual language. Topics include the evolution of Deaf-centered sound art, the intersection of disability and cultural access; and Kim's role in the new disability arts movement.